2017
DOI: 10.1084/jem.20170681
|View full text |Cite
|
Sign up to set email alerts
|

Resolvins suppress tumor growth and enhance cancer therapy

Abstract: Cancer therapy reduces tumor burden by killing tumor cells, yet it simultaneously creates tumor cell debris that may stimulate inflammation and tumor growth. Sulciner et al. demonstrate that specific resolvins (RvD1, RvD2, and RvE1) inhibit tumor growth and enhance cancer therapy through the clearance of tumor cell debris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
305
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(315 citation statements)
references
References 98 publications
8
305
1
1
Order By: Relevance
“…The phenotypic status of monocytes/macrophages are also essential in the pathogenesis of atherosclerosis and injury-induced neointimal hyperplasia (63,64). We and others have previously reported that RvE1 facilitates the resolution of inflammation by enhancing macrophage-mediated phagocytosis of apoptotic neutrophils (65), suppressing monocyte recruitment in ischemic hearts (24), and counterregulating the release of proinflammatory cytokines/chemokines by macrophages (66). These effects are mediated by the ChemR23 receptor (24).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic status of monocytes/macrophages are also essential in the pathogenesis of atherosclerosis and injury-induced neointimal hyperplasia (63,64). We and others have previously reported that RvE1 facilitates the resolution of inflammation by enhancing macrophage-mediated phagocytosis of apoptotic neutrophils (65), suppressing monocyte recruitment in ischemic hearts (24), and counterregulating the release of proinflammatory cytokines/chemokines by macrophages (66). These effects are mediated by the ChemR23 receptor (24).…”
Section: Discussionmentioning
confidence: 99%
“…These results show that various HFA products can be prepared from wild‐type and mutant enzymes at the preparative scale and isolated in good yields in enantiopure form. Because HFA derivatives of C 20 FAs are important lipid mediator molecules with anti‐inflammatory activity and therapeutic potential, further engineering of hydratases can contribute to green stereoselective routes for the enzymatic synthesis of desired hydroxy derivatives of EPA and AA for medical research. Moreover, all C 18 and C 20 HFAs produced by wild‐type and mutant enzymes can be tested for authentic biological activity alone or as components of FAHFAs, as well as for their physicomechanical properties for various bioplastic applications …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the exploration of potential secondary outcomes is beyond the scope of this paper, as it is the understanding of mechanisms that may be utilized by LCPUFAs‐ω3 to delay the progression to a pathological manifestation of obesity. This is important because it is known that resolvins (lipidic mediators derived from the LCPUFAs‐ω3 DHA) acutely turn off inflammation and stimulate a class of immune cells that limit or offset the cytokines effects on lipotoxicity . Based on this, the efficacy of adding DHA or resolvins to the existing therapies used to prevent disease progression is under investigation in other inflammatory diseases such as eczema, periodontal disease, and cancer.…”
Section: Discussionmentioning
confidence: 99%